2022
DOI: 10.1111/tpj.16061
|View full text |Cite
|
Sign up to set email alerts
|

Arabinogalactan protein polysaccharide chains are required for normal biogenesis of plasmodesmata

Abstract: SUMMARY Arabinogalactan proteins (AGPs) are a plant‐specific family of extracellular proteoglycans characterized by large and complex galactose‐rich polysaccharide chains. Functional elucidation of AGPs, however, has been hindered by the high degree of redundancy of AGP genes. To uncover as yet unexplored roles of AGPs in Arabidopsis, a mutant of Hyp O‐galactosyltransferase (HPGT), a critical enzyme that catalyzes the common initial step of Hyp‐linked arabinogalactan chain biosynthesis, was used. Here we show,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…It should be highlighted that AGPs are prime mediators between the cell wall, the plasma membrane, and the cytoplasm [ 53 ]. AGPs also impact symplastic transport following changes in the plasmodesmata structure, acting through the regulation of cell wall properties surrounding the plasmodesmata [ 54 ]. For these reasons, the presence of AGPs in pedestal cells is not surprising, given their function.…”
Section: Discussionmentioning
confidence: 99%
“…It should be highlighted that AGPs are prime mediators between the cell wall, the plasma membrane, and the cytoplasm [ 53 ]. AGPs also impact symplastic transport following changes in the plasmodesmata structure, acting through the regulation of cell wall properties surrounding the plasmodesmata [ 54 ]. For these reasons, the presence of AGPs in pedestal cells is not surprising, given their function.…”
Section: Discussionmentioning
confidence: 99%
“…1 ). AGPs influence on signalling pathways via wall changes was shown in hpgt1,2,3 triple mutants that showed a reduction in cellulose, accumulation of pectin and disrupted plasmodesmata structure ( Okawa et al, 2022 ). Mutants showed stomatal patterning defects that are proposed to result from increased symplastic transport of signalling molecules, such as the transcription factor SPEECHLESS, through larger plasmodesmata cavities ( Okawa et al, 2022 ).…”
Section: Agps and Signallingmentioning
confidence: 99%
“…AGPs influence on signalling pathways via wall changes was shown in hpgt1,2,3 triple mutants that showed a reduction in cellulose, accumulation of pectin and disrupted plasmodesmata structure ( Okawa et al, 2022 ). Mutants showed stomatal patterning defects that are proposed to result from increased symplastic transport of signalling molecules, such as the transcription factor SPEECHLESS, through larger plasmodesmata cavities ( Okawa et al, 2022 ). Involvement of AGPs in embryo development in brown algae and gametophore cell wall development in the moss Physcomitrium patens suggest signalling roles were established early in evolution ( Teh et al, 2022 , Herve et al, 2016 ).…”
Section: Agps and Signallingmentioning
confidence: 99%
“…A high abundance of rhamnogalacturonan I (RG-I) pectins was observed with this approach. In a separate study, Okawa et al (2023) showed that loss of arabinogalactan proteins (AGPs) unexpectedly altered the permeability of A. thaliana PD. The close association between AGP and RG-I ( Tan et al, 2023 ), and the abundance of the latter at PD ( Paterlini et al, 2022 ), suggest that these glycoproteins might also be local, important PD components.…”
Section: Introductionmentioning
confidence: 99%